Extraction of anthocyanins from jambolan fruit using ethanol and deep eutectic solvents: Bioactivity, cytotoxicity, and application as a natural colorant - Pedro Victor Crescêncio de Freitas; Carlos Eduardo de Araújo Padilha; Marcos dos Santos Lima; Patrícia Prado Augusto; Patrícia Santos Lopes; Cristiane Fernandes de Assis; Emanuel Neto Alves de Oliveira; Francisco Caninde de Sousa Junior (PLoS ONE, 2026)
This study aimed to evaluate the extraction of anthocyanins from jambolan ( Syzygium cumini ) fruit using choline chloride-based deep eutectic solvents (DESs) as co-solvents in ethanolic systems. The extraction was performed using ethanol and choline chloride-based DESs with xylitol (ChX-DES) and glycerol (ChG-DES). The highest anthocyanin extraction was achieved using ethanol with 5% DES, resulting in 20.40 to 23.36 mg M3G/ 100 g. Increased temperature favored the extraction, particularly at 70 °C for 5% ChG-DES, yielding 28.92 mg M3G/100 g. The ethanol containing 5% ChG-DES extract exhibited higher color intensity, suggesting its potential as a natural colorant. Additionally, DES-containing extracts demonstrated higher antioxidant capacity and α-amylase and amyloglucosidase inhibition. Cytotoxicity in the HaCaT cell revealed no toxicity up to 12.5 mg/mL. Finally, the color stability of yogurts enriched with the ChG-DES extract was maintained during storage, highlighting the potential of DESs for extracting and applying anthocyanins as natural colorants and functional agents in foods.